Insider perspectives: insights from formers on their role as subject-participants in P/CVE research - Malet, David; Galloway, Brad; Farrell-Molloy, Joshua; Örell, Robert; Shaikh, Mubin; Lopez-Jauffret, Charlotte; Lynch, Sarah; West, Jennifer (Journal of policing, intelligence and counter terrorism, 2025)
This article examines the contributions of 'formers', individuals who were previously affiliated with groups advocating violent extremism but who now work as researchers and practitioners in the P/CVE field. There are a limited number of studies assessing the value added of formers to P/CVE programs. We make two significant contributions to the body of work. First, we examine how formers can contribute not only to P/CVE practice, but to academic research of terrorism, and how their insights and experience can be employed for improving research designs and interview completion rates and responses. Second, none of the extant works incorporates the views of formers themselves in the assessments. Four of the co-authors of this article are formers who publish peer-reviewed and policy institute research, and they present their perspectives on who counts as a former, and how their individual backgrounds inform and bolster their research and praxis. We encourage researchers of political violence to emulate other fields of social science and incorporate appropriately trained formers as subject-participants to improve research in the field.